2019
DOI: 10.1016/j.sjbs.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Eye color prediction using single nucleotide polymorphisms in Saudi population

Abstract: BackgroundDNA prediction of eye color represent one application of the externally visible characteristics (EVC), which attained growing interest in the field of DNA forensic phenotyping. This is mainly due to its ability to narrow the pool of suspects without the need to compare any retrieved DNA material from the crime scene to a reference DNA. Several methods and multiplex genetic panel were proposed with variable prediction accuracy between different populations. However, such panel was not previously teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…These deviations provide an indication of the association with Shapturenko et al, (2019) 9 . A study in Saudi population 10 observed the SNP rs1800407 was not polymorphic in the Saudi population with the presence of the allele G. In this study, concluded the rs1800407 indicating of eye color with the rs12913832 because of the linkage disequilibrium coefficient between alleles of these SNPs strong associated with eye color.…”
Section: Discussionmentioning
confidence: 56%
“…These deviations provide an indication of the association with Shapturenko et al, (2019) 9 . A study in Saudi population 10 observed the SNP rs1800407 was not polymorphic in the Saudi population with the presence of the allele G. In this study, concluded the rs1800407 indicating of eye color with the rs12913832 because of the linkage disequilibrium coefficient between alleles of these SNPs strong associated with eye color.…”
Section: Discussionmentioning
confidence: 56%
“…A t-statistic is determined in this method to compare the averages of the two marker genotype groups. The F-statistic is used for more than two potential genotypes [ 11 ]. There are various approaches, including score checks, logistic regression, and Bayesian methods, for Haplotype association with a phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…LowerT hreshold = (1 − T hreshold/100) * maxF ullM utation (11) selectedSN P s = minF ullM utation <= LowerT hreshold…”
Section: Snps Preselectionmentioning
confidence: 99%
“…We also tested the proposed approach onType-2 diabetes phenotype. We considered different linear thresholds and the results for the optimal number of SNPs are summarized in table 11. Figure 12 and 13 shows the Confusion matrix and AUC of the best classification results.…”
Section: Type-2 Diabetes Predictionmentioning
confidence: 99%